Sources of Difficulty in Counselling Sexual Abuse Victims and Survivors - McBride, Martha C.; Markos, Patricia A. (Canadian Journal of Counselling and Psychotherapy, 2007)
During the last decade, societal awareness of the problem of sexual abuse of children has reached unprecedented heights, and one result has been an increase in the reporting of childhood sexual abuse. Since the psychological effects of childhood sexual abuse impacts the functioning of both children and adults, a practicing counsellor in any setting will probably encounter clients who have experienced childhood sexual abuse. This article will look at problems both counsellors and clients face when confronting dysfunctional behaviour and symptoms resulting from sexual abuse.